PELAYANAN PELATIHAN PETUGAS PEMERIKSA KESEHATAN JEMAAH HAJI DI UPT. PENANGGULANGAN KRISIS KESEHATAN PENGAMBANGAN SUMBER DAYA MANUSIA DAN KESEHATAN OLAHRAGA MASYARAKAT DINAS KESEHATAN PROVINSI RIAU - Aladin Aladin; Isjoni Isjoni; Azhar Azhar (Universitas Riau, 2020)
The profile of Indonesian hajj in the last ten years belongs to high risk groups that could endanger safety and health of hajj in theirperformingatTanah Suci. The Government of Indonesia through the Ministry of Health has taken a strategic step in improving health of indonesian hajj by conducting training of Hajj Health Check Officer (HHCO). This research includes of qualitative research with interview data collection techniques and documentation.Service of training hajj health check officerconsists of three aspects, namely planning, implementation, and evaluation. Planning is arranged systematically so that the organizing committee can work in accordance with duties and functions. Implementation of training is carried out in accordance with planned curriculum and training schedule. The service of training implementation can be seen from pre-process of learning, learning process, and closing of training. Furthermore, evaluation of training consists of three components, namely evaluation of participants, evaluation of facilitator and evaluation of organization. Evaluation results show that participants understand the training materials provided. Evaluation results of facilitator indicate that facilitator can convey their knowledge and skills well to participants. And evaluation results of organization shows that participants are satisfied with training organizer. Based on the evaluation of participants, facilitators, and organizers, it can be concluded that training service of HHCO at UPT.Penanggulangan Krisis Kesehatan Pengembangan Sumber Daya Manusia and Kesehatan Olahraga Masyarakat Dinas Kesehatan Provinsi Riau are considered good. Training of HHCO have provided knowledge and insight in accordance with the field of work.